KEPUASAAN DAN KESETIAAN KONSUMEN PADA WAKTU TUNGGU DELAY PESAWAT TERBANG - Parsetiorini, Okkytania E. (Fakultas Ekonomi Universitas Islam 45, 2017)
This research focuses on the perception of the factors that influence satisfaction during delay, such as the perceived waiting time, satisfaction with delay information obtained, and satisfaction of environmental conditions during the waiting time, to the waiting time satisfaction and their influence on customer satisfaction and loyalty of customers in the aviation business at Adisucipto airport, Yogyakarta. This study analyzed by multiple regression analysis. This study found that there is a significant and positive effect of satisfaction with waiting environment on waiting satisfaction and customer satisfaction directly and the waiting time satisfaction does not have a moderating effect on the relationship of customer satisfaction and customer loyalty.